Brothers in exile: Masonic lodges and the refugees of the Haitian Revolution, 1790s–1820. Issue 3 (3rd July 2019) - Jansen, Jan C.
ABSTRACT: In the wake of the Haitian Revolution (1791–1804), tens of thousands of people – white colonists, free people of color, and slaves – left the French colony of Saint-Domingue for neighboring Caribbean colonies and North America. Scattered and diverse as they were, these refugees maintained diasporic bonds, constituting a community with distinct social, cultural, linguistic, and religious traits. Fraternalism, and Masonic lodges in particular, played a pivotal role in shaping these connections. Based on new empirical evidence from the major centers of the refugee community (the US, Louisiana, Cuba, Jamaica), this paper examines the emergence of these refugee lodges. Placing them in their social contexts and analyzing their membership practices, it argues that Freemasonry provided an important social infrastructure for a segment of the refugee population – an infrastructure that was used to cultivate diasporic connections, to (re)enhance internal hierarchies, and to build networks in the host societies.